2017
DOI: 10.3390/molecules22060870
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, and Antioxidant Activity Evaluation of Liposomes Containing Water-Soluble Hydroxytyrosol from Olive

Abstract: Due to the multiple hydroxyl groups in its structure, hydroxytyrosol (HT) is very sensitive to air and light and has very strong instability and hydrophilicity that affect its biological activity. This study attempted to prepare liposomes containing water-soluble HT to improve the bioavailability and biocompatibility of the target drug. The preparation process factors (temperature, mass ratio of phospholipid (PL) and cholesterol (CH), Tween-80 volume, HT mass) were studied and response surface methodology (RSM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…Pinsuwan et al (79) demonstrated the enhanced antioxidant activity of liposomes encapsulating extract of Hibiscus sabdariffa using an in vitro skin model. A similar in vitro activity enhancement using liposome-based encapsulation of natural products has been reported by other researchers using different methods (78,80). Feng et al evaluated the in vivo effect of liposomal encapsulation of chlorogenic acid following oral administration in mice.…”
Section: Antioxidant Assaysupporting
confidence: 65%
“…Pinsuwan et al (79) demonstrated the enhanced antioxidant activity of liposomes encapsulating extract of Hibiscus sabdariffa using an in vitro skin model. A similar in vitro activity enhancement using liposome-based encapsulation of natural products has been reported by other researchers using different methods (78,80). Feng et al evaluated the in vivo effect of liposomal encapsulation of chlorogenic acid following oral administration in mice.…”
Section: Antioxidant Assaysupporting
confidence: 65%
“…The maximum LC value was obtained at the ratio of 8:1. Many reports have demonstrated that the stability and EE of liposomes could be enhanced by adding an appropriate amount of Tween 80 in the formulation (Lu et al., ; Yuan, Qin, Tu, & Li, ). This might be attributed to the steric stabilization provided by Tween 80.…”
Section: Resultsmentioning
confidence: 99%
“…Liposomes are spherical phospholipid bilayers that mimic cellular structures and can be used as model membrane systems. They are widely used as xenobiotic delivery systems since they improve the availability of the active compound, target and slow its release, and show protective features [ 44 ]. This is why liposomes have potential applications in a wide range of fields, including pharmaceutical sciences, food technology, or agriculture.…”
Section: Resultsmentioning
confidence: 99%